A Class of Sextic Trigonometric Bézier Curve with Two Shape Parameters - Salma Naseer; Muhammad Abbas; Homan Emadifar; Samia Bi Bi; Tahir Nazir; Zaheer Hussain Shah (Journal of Mathematics)
In this paper, we present a new class of sextic trigonometric Bernstein (ST-Bernstein, for short) basis functions with two shape parameters along with their geometric properties which are similar to the classical Bernstein basis functions. A sextic trigonometric Bézier (ST-Bézier, for short) curve with two shape parameters and their geometric characteristics is also constructed. The continuity constraints for the connection of two adjacent ST-Bézier curves segments are discussed. Shape control parameters can provide an opportunity to modify the shape of curve as designer desired. Some open and closed curves are also part of this study.